THE CLINICAL FEATURES AND PROGNOSIS OF SCAN NEGATIVE URO-NEUROLOGICAL DISORDERS. Issue 12 (15th November 2016) - Hoeritzauer, Ingrid; Panicker, Jalesh; Elneil-Coker, Sohier; Granitsiotis, Voula; Small, Doug; Statham, Patrick; Summers, David; Eugenicos, Maria; Carson, Alan; Stone, Jon
Abstract : Background: Studies from our group have shown that around half of patients presenting with cauda equina syndrome (CES) have normal imaging, many of whom may have evidence of a functional neurological disorder. We have also shown high rates of comorbidity of functional neurological disorders in patients with idiopathic chronic urinary retention (including Fowler's syndrome). Aims: To determine what proportion of patients with 'scan negative' CES and chronic dysfunctional voiding have a functional disorder by clinical consensus. To determine distress, disability and ongoing symptoms in patients with 'scan positive' and 'scan negative' CES three months after symptom onset. To determine frequency of comorbid functional disorders, distress, disability and physical function in patients with voiding dysfunction and a control urological group. Project Plans: The Back or Leg Pain with Bladder symptoms study (BLB) study is a prospective case control study of all patients admitted with possible CES to the Western General Hospital, Edinburgh. The Overview of Comorbidity in Chronic Urinary Retention (OCCUR) study is a prospective cohort study and retrospective notes review of patients with Chronic Urinary Retention (including Fowler's syndrome) via the urodynamic clinics in Glasgow, Edinburgh and London.